Diagnosed ophthalmopathy in domestic rodents, rabbits and aquatic turtles from Havana, Cuba. Period 2007-2020 - Hugues, Beatriz (2022)
The aim of this study was to describe ophthalmic conditions diagnosed at the main veterinary clinic in Havana, Cuba, between 2007 and 2020 in the golden hamster (Mesocricetus auratus), guinea pigs (Cavia porcellus), rabbits (Oryctolagus cuniculus), and aquatic turtles (Trachemys decussata). The sample was made up of 528 animals (174 golden hamsters, 116 guinea pigs, 72 rabbits and 166 turtles) of various ages and sexes. Hamsters were the most attended (33%), followed by turtles (31%), while 55% of these animals were female. Oculars prolapse was more frequent in hamsters (62/174), guinea pigs showed a higher frequency of blepharitis (62/116), conjunctivitis predominated in rabbits (38/72) and blepharoconjunctivitis in turtles (151/166). The main causes were mainly due to the poor breeding system and ignorance, which leads to injuries, accidents, lack of hygiene and fighting between animals.